Пошаговое объяснение:
cos2a/(1-sin2a) = (1+tga)/(1-tga)
(cos²a - sin²a)/(cos²a + sin²a - 2 cosa ·sina) = (1+tga)/(1-tga)
(cos²a - sin²a)/(cosa - sina)² = (1+tga)/(1-tga)
(cosa + sina)/(cosa - sina) = (1+tga)/(1-tga)
(1 + sina/cosa)/(1 - sina/cosa) = (1+tga)/(1-tga)
(1+tga)/(1-tga) ≡ (1+tga)/(1-tga)
тождество доказано
Белоствольная береза
прелестная тишина
густой лес
веселое утро
<span>а)-7,6+10,9-(-7,6)-1,9+1,09=-7,6+10,9+7,6-1,9+1,09=
=(-7,6+7,6)+(10,9-1,9)+1,09=0+9+1,09=10,09
</span><span>б)4/7*(-9)-4/7*5=4/7*(-9-5)=4/7*(-14)=48-2=-8
</span><span>в)(20 4/5+1 5/12-0,8-3.1/3)*1/6.=108,5
1)20 4/5-0,8=20,8-0,8=20
2)20+1 5/12=21 5/12
3)21 5/12-3 1/3=21 5/12-3 4/12=18 1/12
4)18 1/12*1/6=217/12*1/6=217/2=108,5</span>
248:4=62; 507+4893=1350×4
0,3*(х-4)=0,8*(3х-11)
0,3х-1,2=2,4х-8,8
0,3х-2,4х=-8,8+1,2
-2,1х=-7,6
х= 7 6/10:2 1/10=(76*10)/10*21=76/21=3 13/21